Comparative Analysis of Abnormal Returns of Stocks and UBS Gold Before and After the Announcement of the Covid-19 Pandemic - Qamaral Shabrina Agfah; Muhammad Azhari (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Currently, the economy and capital market in Indonesia are experiencing a decline in performance due to the COVID-19 pandemic. This research was conducted to analyze whether there is a difference in the return of shares in the transportation sub-sector and UBS gold to the current COVID-19 pandemic, by looking at changes in prices 7 days before and 7 days after the announcement of the COVID- 19 Pandemic announced by President Joko Widodo on March 2, 2020. The phenomena contained in this study were carried out by the event study with the abnormal return technique. This study using data in the form of secondary data and data taken by time series. The sample used in this research is data on the closing price of 7 days of 1-gram UBS pure gold before and after the COVID-19 pandemic and 23 shares of the transportation sub-sector listed on the Indonesia Stock Exchange. Data analysis used abnormal return, normality test, and paired sample t-test using IBM SPSS. This study found that there was no difference in the abnormal return of shares in the transportation sub-sector and UBS Gold at the time of the announcement of the COVID-19 pandemic in Indonesia by Joko Widodo.